Evaluation of Demographic and Clinical Characteristics of Patients who Attempted Suicide by Self-Inflicted Burn Using Catalyzer - Yabanoglu, Hakan (Int Surg, 2015)
Our aim was to assess demographic and clinical characteristics of patients treated at our units who attempted suicide by self-incineration, and to compare the results of burns with or without catalyzer use. Twenty patients who attempted suicide by self-incineration were examined in terms of clinical and demographic characteristics. Average age of the study population was 35 years (range 13−85 years). Average percentage of total body surface area burn was 53% (9%−100%). Six (30%) patients used gasoline and 5 (25%) used paint thinner in order to catalyze burning. Of these 11 patients who used a catalyzer, 5 (45.4%) had inhalation injury and 7 (63.6%) died. Among 9 patients who did not use any catalyzer, 1 (11.1%) had inhalation injury and 4 (44.4%) died. In general, inhalation injury was diagnosed in 6 patients (30%) while 11 (55%) patients died. A high morbidity and mortality rate was found in patients who used a catalyzer.